PROFILE OF SCHOOL READINESS IN APPLYING STEM (SCIENCE, TECHNOLOGY, ENGINEERING, MATHEMATIC) EDUCATION - Yanti Herlanti; Usawatun Amalia; Ai Nurlaela (EDUSAINS, 2022)
STEM knowledge and skills are needed by students in order to survive in the era of the industrial revolution 4.0. This study aims to determine the level of readiness of public high schools in Bogor City in implementing STEM education. Descriptive research with survey method with stratified sample selection. The number of samples is three principals, nine science teachers, and 75 students. The research instrument was in the form of a questionnaire assessing readiness from aspects of the curriculum, supporting extracurriculars, admission selection, and STEM supporting facilities as well as students' interest in STEM. Data analysis uses a modified readiness score according to Aydin & Tascy (2005). The findings of the study show that public high schools in the city of Bogor are ready to implement STEM education. Readiness to apply STEM education is shown by the Principal. Students also showed readiness to apply STEM education, but needed a little improvement. As for the teacher, it shows unpreparedness and needs improvement.